(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Taisiya I. Skorobogatova, Tatyana A. Shkuratova (Rostov-on-Don, Russian Federation) This article is a continuation of the authors’ research, the first results of which were published in the article “Pride and Prejudice”: the Anglicization of the French Language and the Gallicization of the English Language (2018). This time, the vector of consideration of two historically interdependent phenomena, the interactional nature of which continues for 900 years (from the conquest of England by the Normans to the end of World War II) of the anglicization of the French language and the gallicization of English, became the level of the phraseological system. The purpose of the article is to state the mutual enrichment of national phraseological funds and the replenishment of the system of images. The interaction of English and French in the field of phraseological borrowing is due to the fact that phraseological borrowing is the result of the interaction of these two languages and the history of two peoples, including the formation and development of their literature. The duration of language contact has provided the ability to perceive emotional images in which reality is displayed, even in the presence of different mentalities and different national traits. Key words: Anglicization, French, gallicization, English, phraseology, phraseological composition, phraseological borrowing, calque. DOI 10.23683/1995-0640-2019-1-99-107